Identification of the key genes in children with sepsis by WGCNA in multiple GEO datasets - Shen, Yue-chuan; Yu, Dao-jun; Yu, Ze; Zhao, Xue (Frontiers in Pediatrics, 2025)
Pediatric sepsis is a serious condition causing organ failure owing to immune dysregulation, linked to high morbidity and mortality, highlighting the need for quick detection and treatment. This study aims to identify key genes involved in pediatric sepsis using three gene expression datasets from the Gene Expression Omnibus. We first identified differentially expressed genes (DEGs) with R, then conducted a gene set enrichment analysis, and integrated DEGs with important module genes from weighted gene coexpression network analysis. We also screened adult sepsis datasets to find genes specific to pediatric cases, ultimately validating XCL1 as a key gene. This study suggests that XCL1 is crucial in understanding pediatric sepsis etiology and its molecular mechanisms.